ANALISIS MARKA MORFOLOGI DAN MOLEKULER SIFAT KETAHANAN KEDELAI TERHADAP INTENSITAS CAHAYA RENDAH - Handayani, Titin; Sastrosumarjo, Sarsidi; Sopandie, Didy; Suharsono, Suharsono; Setiawan, Asep (Jurnal Sains dan Teknologi Indonesia, 2006)
Availability of moleculer marker to identify the important agronomic character of plant is needed to accelerate selection activity of plant. Particularly for the complex quantitatively inherited traits - like e.g. shading tolerance of soybean - the use of such a technique will speed up the process to produce adapted genotypes.The objective of this research is to identify the linkage of molecular marker RAPD with character of shading tolerance. The morphological specific characters wich is corelated to shade tolerance is the number of productive branchs. The intensity 75% of artificial shading is optimal level for doing selection of soybean genotypes. The inheritance of shading tolerance of soybean was controlled by gene with full dominant or by two genes pairs with dominant and ressesive epistasis. There was no maternal effect in the inheritance to shade tolerance. Heritability value (0.45 – 0.54) indicated that the proportion variation caused by the genetic factors was moderate. Molecular analysis by using RAPD technique showed that UBC153, ROTH 480.01, and ROTH 480.03 primer have polymorphic band that can be used for inheritance study and linkage analysis. All polymorphisms segregated independently of each ather. Interval mapping with Mapmaker/QTL indicated that the location of the three QTLs on linkage group were at marker tolerance locus of Roth 480.01-8125 , Roth 480.03-1125, and UBC 153-19125 .